2022
DOI: 10.1038/s41565-021-01038-4
|View full text |Cite
|
Sign up to set email alerts
|

Fully integrated parity–time-symmetric electronics

Abstract: Harnessing parity–time symmetry with balanced gain and loss profiles has created a variety of opportunities in electronics from wireless energy transfer to telemetry sensing and topological defect engineering. However, existing implementations often employ ad hoc approaches at low operating frequencies and are unable to accommodate large-scale integration. Here we report a fully integrated realization of parity–time symmetry in a standard complementary metal–oxide–semiconductor process technology. Our work dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 50 publications
(78 reference statements)
0
16
0
Order By: Relevance
“…Particularly, the influence of optical gain and the slab thickness on the directionality of transition radiation remains elusive, while a larger optical gain is generally thought to have a larger enhancement of the intensity of transition radiation. More rich physics of free-electron radiation could be expected in systems simultaneously with optical gain and optical loss, such as those with parity-time symmetry [183][184][185][186][187]. However, the influence of the interplay between optical gain and optical loss on the transition radiation has never been explored before.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, the influence of optical gain and the slab thickness on the directionality of transition radiation remains elusive, while a larger optical gain is generally thought to have a larger enhancement of the intensity of transition radiation. More rich physics of free-electron radiation could be expected in systems simultaneously with optical gain and optical loss, such as those with parity-time symmetry [183][184][185][186][187]. However, the influence of the interplay between optical gain and optical loss on the transition radiation has never been explored before.…”
Section: Discussionmentioning
confidence: 99%
“…For example, one can transmit the signal with extremely low loss 46 and devise the multiplexing 47 and imaging 48 with these topologically boundary modes. Recently, it is shown that the topological LC circuit can be fully integrated by complementary metal-oxide-semiconductor (CMOS) technology 49 , 50 , which may solve the outstanding challenges met in the chip industry. Our findings may stimulate the effort in the broad physics and materials community to look for real materials that support SHOWS, since we have provided a rather general framework to construct the Hamiltonian.…”
Section: Discussionmentioning
confidence: 99%
“…[4,12,13] Fully integrated devices that allow full functionality but unrequire external accessories are hailed as one of the most ideal and ultimate goals for modern device design and development. [14][15][16][17] The introduction of the fully integrated concept into the wearable biochemical sensing, the fully integrated wearable biochemical sensors enable the wireless, noninvasive, continuous, and multiplexed in situ tracking of biomarkers at molecular levels for potential health situation evaluation and management on a daily basis. Since the pioneered work on the fully integrated wearable sweat sensor was demonstrated by Javey's group from University of California Berkeley in 2016, [18] prolific fully integrated wearable biochemical sensors for either epidermal sweat or wound exudate tracking have been developed.…”
Section: Research Articlementioning
confidence: 99%